Feeding Monensin to yearling cattle on summer grass - Smith, E.F.; Pruitt, R.; Riley, Jack G.; Corah, L.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
The feed additive, Monensin, was self-fed in a feed block to yearling cattle on summer pasture. Consumption of the block (0.29 lb. daily) supplied 116 mg. of Monensin daily, which failed to improve the cattle’s performance.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Monensin; Yearling cattle